A qualitative exploration of how university students access sexual health services. - Hainey, Lyndsey (2011)
Current trends show only a measured reduction in the number of newly acquired sexually transmitted infections despite an increase in the level of funding to sexual health services and more extensive sex education in schools (DH 2009b: DH2007a). Factors that influence and motivate vulnerable individuals to access sexual health services are key determinants in the reduction of sexually transmitted infections (Dixon-Wood et al, 2001). This study took a qualitative methodological approach to understanding how non-healthcare related university students access sexual health services. This included an exploration of the influences and motivations behind service access as well as participants’ suggestions for improvement to sexual health services. Such research is valuable in understanding the factors which influence service accessibility and the high prevalence of sexually transmitted infections within the student population. Data was gathered using a semi-structured, face to face interview process. A saturation of data was achieved after eleven interviews. Findings indicated that there were two key factors which influenced access to sexual health services: whether services allowed participants to retain control over their health experience; and services known for the non-judgemental attitudes of the professionals involved in service provision. Participants also suggested a number of improvements to sexual health services such as ensuring a greater commitment to the empowerment of service users and tailoring sexual health services to the individual. Several recommendations for future research and nursing practice were made to improve service uptake and the overall satisfaction of service users which is vital if individuals are to continue using sexual health facilities. Recommendations for nursing practice include providing mandatory sexual health training for service providers and granting greater service user autonomy. Recommendations for future research include investigating how the motivations of individuals who have never accessed sexual health services before compare to experienced service users.